Lichen response to ammonia deposition defines the footprint of a penguin rookery - Crittenden, P.D.; Scrimgeour, C.M.; Minnullina, G.; Sutton, M.A.; Tang, Y.S.; Theobald, M.R. (Springer, 2015)
Ammonia volatilized from penguin rookeries is a major nitrogen source in Antarctic coastal terrestrial ecosystems. However, the spatial extent of ammonia dispersion from rookeries and its impacts have not been quantified previously. We measured ammonia concentration in air and lichen ecophysiological response variables proximate to an Adèlie penguin rookery at Cape Hallett, northern Victoria Land. Ammonia emitted from the rookery was 15N-enriched (δ15N value +6.9) and concentrations in air ranged from 36–75 µg m−3 at the rookery centre to 0.05 µg m−3 at a distance of 15.3 km. δ15N values and rates of phosphomonoesterase (PME) activity in the lichens Usnea sphacelata and Umbilicaria decussata were strongly negatively related to distance from the rookery and PME activity was positively related to thallus N:P mass ratio. In contrast, the lichen Xanthomendoza borealis, which is largely restricted to within an area 0.5 km from the rookery perimeter, had high N, P and 15N concentrations but low PME activity suggesting that nutrient scavenging capacity is suppressed in highly eutrophicated sites. An ammonia dispersion model indicates that ammonia concentrations sufficient to significantly elevate PME activity and δ15N values (≥0.1 µg NH3 m−3) occurred over c. 40–300 km2 surrounding the rookery suggesting that penguin rookeries potentially can generate large spatial impact zones. In a general linear model NH3 concentration and lichen species identity were found to account for 72 % of variation in the putative proportion of lichen thallus N originating from penguin derived NH3. The results provide evidence of large scale impact of N transfer from a marine to an N-limited terrestrial ecosystem.